Dampak Produktivitas, Reproduksi, dan Pemulihan pada Remaja dengan Concurrent Stunting–Overweight/Obesity (Cso): Literature Review (Lembaga Pengembangan Kinerja Dosen, 2026)
Concurrent stunting and overweight/obesity (CSO) in adolescents represents a complex form of the double burden of malnutrition, characterized by linear growth faltering coexisting with excess body fat. This condition poses significant metabolic, cognitive, and reproductive risks that may affect long-term health and productivity. This review employs a narrative literature approach by synthesizing evidence from PubMed, Scopus, Web of Science, Google Scholar, and national journal portals. Included literature comprises studies assessing stunting, overweight/obesity, metabolic risk, cognitive function, and reproductive health among adolescents. Indonesian evidence (Harits et al., 2024) indicates that obese adolescents with a history of stunting exhibit a higher prevalence of metabolic syndrome (18.75%), greater abdominal adiposity, and elevated systolic blood pressure compared to non-stunted obese peers. Biologically, stunting impairs neurocognitive development and reduces muscle mass, while obesity promotes metabolic inflammation; the coexistence of these factors may reduce physical fitness, learning capacity, and overall productivity. CSO also affects reproductive health, including increased risks of ovulatory dysfunction, delayed sexual maturation, and intergenerational nutritional disadvantages. Although linear growth recovery is limited due to epiphyseal closure, functional recovery through improved diet quality and physical activity remains possible. In conclusion, adolescents with CSO experience greater metabolic, cognitive, and reproductive vulnerabilities than those affected by stunting or obesity alone. Interventions emphasizing metabolic function, diet quality, physical fitness, and reproductive health preparation are essential to prevent long-term consequences and break the intergenerational cycle of malnutrition. Further national research is required to map the prevalence and implications of CSO comprehensively.